RHIZOSPHERE MICROBIOME, SOIL ENZYMES AND GROUNDNUT YIELD AS INFLUENCED BY ADDITION OF BIOCHAR AND FERTILIZERS IN IRRIGATED ALFISOL OF NORTH COASTAL ANDHRA PRADESH - B. GOWTHAMI; P. GURUMURTHY* (The Journal of Research ANGRAU, 2024)
The field experiment was conducted in irrigated Alfisols of North coastal Andhra Pradesh to study the effect of biochar and chemical fertilizers on rhizosphere microbiome, soil enzymes and yield performance of groundnut crop (variety K-6) during rabi, 2018-19. Biochar application to soil significantly increased soil bacterial, fungal and actinomycetes population. At pod development stage, the highest number of bacterial count (39.0 x106 CFU g-1 soil) was observed in T5 (100% RDF + biochar @ 6 t ha-1) which was on par with all the biochar applied treatments (T3, T4 , T6, T7 , T8 ). The Biochar applied @ 6 t ha-1 (T5 & T8 ) significantly increased the bacterial population as compared to non-biochar applied treatments (T1 & T2). Fungal and actinomycetes population followed the similar trend of bacterial count. Soil urease activity was significantly superior in biochar applied treatments (T3, T4, T5, T6, T7, T8) compared to non biochar applied treatments (T1 and T2). With increased rates of biochar application the urease activity markedly increased in soil. Similar trend was noticed with respect to dehydrogenase, acid phosphatase and alkaline phosphatase enzymes in soil in response to addition of biochar. At pod development stage, the highest leaf area index (3.16) was recorded with 100% RDF + biochar @ 6 t ha-1(T5 ) which was significantly higher than T1 (control), T2 (100% RDF) and T6 (75% RDF + biochar @ 2 t ha-1). The highest drymatter accumulation of 2951 kg ha-1 at peg penetration and 6428 kg ha-1 at pod development was observed in T5 (100% RDF + biochar @ 6 t ha-1) which was on par with T3 (100% RDF + biochar @ 2 t ha-1), T4 (100% RDF + biochar @ 4 t ha-1), T8 (75% RDF + biochar @ 6 t ha-1) treatments. Groundnut pod yield was highest (4019.58 kg ha-1) in treatment received 100% RDF + biochar @ 6 t ha-1, which was on par with T4 (100% RDF + biochar @ 6 t ha-1) and T8 (75% RDF + biochar @ 6 t ha-1).